The road to hell is paved with good intentions—A critical evaluation of WADA's anti-doping campaign. Issue 3 (June 2016) - Møller, Verner
Abstract: In 2012 following a foundation board meeting a working group under the World Anti-Doping Agency (WADA) was established in order to investigate the lack of effectiveness of the anti-doping testing programs. The working group identified a number of weaknesses with lack of compliance with the anti-doping code by central stakeholders, as the essential problem. According to the working group human and political factors are the reason why anti-doping has been unsuccessful. There is no critique of WADA and the purpose of anti-doping as such. So the aim of this paper is to measure if world anti-doping – its inadequate harmonization, coordination and effectiveness with regard to detection, deterrence and prevention of doping aside – is generally sound and successful. It does so by exercising a critical examination of the purpose as stated in the World Anti-Doping Code: "To protect the athletes fundamental right to participate in doping-free sport and thus promote health, fairness and equality for athletes worldwide". After a brief introduction to the background for the foundation of WADA followed by an explanation of political success it goes on to evaluate the stated purpose step-by-step. Based on the working groups finding and illustrated by exemplary cases the paper demonstrates that anti doping does not offer any protection of athletes right to participate in doping free sport; that it does not offer significant health protection; and that it does not protect fairness and equality for athletes worldwide. This leads to the conclusion that anti-doping under the auspices of WADA has been unsuccessful and counter-productive.